THE RELATIONSHIP OF THE ROLE OF POSYANDU CADRES ON THE QUALITY OF LIFE OF ELDERLY STROKE SUFFERS IN THE WORKING AREA OF THE MEURAH MULIA COMMUNITY HEALTH CENTER NORTH ACEH - Aina Fitri; Mahruri Saputra; Rehmaita Malem; Nadia Ulfa (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Stroke in the elderly can affect life in various aspects, including physical, psychological, emotional, cognitive and social. This decreased function will have an impact on the quality of life of the elderly. Elderly posyandu cadres have a role in improving the quality of life of the elderly by means of motivation, counseling and regular health monitoring. The aim of this research is to determine the relationship between the role of posyandu cadres and the quality of life of elderly stroke sufferers in the Meurah Mulia Community Health Center working area, North Aceh. This research design uses a quantitative method approachcross sectional study. Population in this study totaling 32 people, namely all elderly stroke patients who were in the working area of the Meurah Mulia Community Health Center, North Aceh. The sampling technique was carried out using the total sampling Which totaling 32 people. Data analysis was carried out univariate and bivariate using tests Chi Square test. Based on the results of the research conducted, it can be seen that there were 19 respondents (59.4%) in the Good category for patient quality of life and 13 respondents (40.6%) in the Poor category. Statistical test results using Chi Square Test obtained value 0.002 < 0.005, then Ho is rejected and Ha is accepted, so it can be concluded that there is a relationship between the role of Posyandu cadres and the quality of life of elderly stroke sufferers in the working area of the Meurah Mulia Community Health Center, North Aceh Regency.